Emerging therapeutic targets for neuromyelitis optica spectrum disorder - Tradtrantip, Lukmanee; Asavapanumas, Nithi; Verkman, Alan S (Expert opinion on therapeutic targets, 2020)
: Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory demyelinating disease of the central nervous system affecting primarily the spinal cord and optic nerves. Most NMOSD patients are seropositive for immunoglobulin G autoantibodies against astrocyte water channel aquaporin-4, called AQP4-IgG, which cause astrocyte injury leading to demyelination and neurological impairment. Current therapy for AQP4-IgG seropositive NMOSD includes immunosuppression, B cell depletion, and plasma exchange. Newer therapies target complement, CD19 and IL-6 receptors. : This review covers early-stage pre-clinical therapeutic approaches for seropositive NMOSD. Targets include pathogenic AQP4-IgG autoantibodies and their binding to AQP4, complement-dependent and cell-mediated cytotoxicity, blood-brain barrier, remyelination and immune effector and regulatory cells, with treatment modalities including small molecules, biologics, and cells. : Though newer NMOSD therapies appear to have increased efficacy in reducing relapse rate and neurological deficit, increasingly targeted therapies could benefit NMOSD patients with ongoing relapses and could potentially be superior in efficacy and safety. Of the various early-stage therapeutic approaches, IgG inactivating enzymes, aquaporumab blocking antibodies, drugs targeting early components of the classical complement system, complement regulator-targeted drugs, and Fc-based multimers are of interest. Curative strategies, perhaps involving AQP4 tolerization, remain intriguing future possibilities.